Evaluating Outcomes of Mechanically Ventilated Neonates: A Single Centered Retrospective Cohort Study - Faiqa Taj, Kiran Israr Shah, Jamal Ashraf, Ayesha Sadia, Faiza Kiran, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The infant mortality rate is considered a main reflector of the state of a community’s public health and social development. Study aimed to find various outcomes observed in neonates receiving mechanical ventilation, investigating different factors such as duration of ventilation, patient demographics, mode of delivery, gestational age group and underlying comorbid conditions. Methods: This retrospective cohort study was conducted in the NICU of Izzat Ali Shah Hospital, Wah Cantt. Data was collected from January 2022 to May 2023. The participant cohort included 153 neonates of both genders (aged 0 to 28 days) through non-probability/consecutive sampling technique, who were placed on mechanical ventilation during their NICU stay. Data was collected on structured performa and analyzed using statistical software SPSS version 11. The analysis included descriptive statistics, mean, median, and standard deviation for continuous variables; frequencies and percentages for categorical variables. Results: The results showed that most of the neonates were delivered via C-Section (f=95, 62.1%). Both genders experienced high mortality with an overall mortality rate of 83 (53.6%). Mortality was highest among patients with extended NICU stays, especially beyond 9 days, where mortality reached 100%. This study also showed that survival rate improved with higher gestational age 21 (28.3%) term patients out of 74. Similarly, shorter ventilation durations are linked to better outcomes i.e. 29 (26.1%) patients who were weaned off within first two days of ventilation survived. Conclusion: The implications of this study advocate the need for initiatives and programs for maximum maternal and neonatal care at government level with multidisciplinary approach in managing ventilated patients as also emphasized in other studies. Keywords: Neonatal; Ventilator; Mortality; Cohort; Intensive care units